Immediate and sustained haemodynamic effects of prazosin during upright exercise in man. Issue 6 (December 1981) - Silke, B; Hendry, W G; Taylor, S H
Abstract : To ascertain the immediate pharmacodynamic and long-term haemodynamic effects of prazosin in chronic ambulant heart failure, measurements were made during sitting, standing, and walking in 12 patients with severe ischaemic left ventricular failure before and after their first dose of prazosin (2 mg) and in six of these patients after a further 12 weeks of sustained treatment (2 mg tds). When first added to treatment with digoxin and frusemide, prazosin was followed within an hour by substantial reductions in systemic arterial, pulmonary arterial, and pulmonary venous pressures in both postures at rest and also during walking. These changes were significantly attenuated after continued treatment. Cardiac output while sitting and standing at rest was reduced in both instances but the response to exercise was unchanged. The pharmacodynamic effects of prazosin in heart failure are explicable in terms of blockade of alpha1 adrenoceptors in arterial resistance and venous capacitance vessels augmented perhaps by lessening of reflex vasoconstriction secondary to the reduction in pulmonary venous pressure. The cause of the attenuation of the acute haemodynamic effects of the drug during sustained treatment is unknown.